Secondary systemic lupus erythematosus after thymoma resection misdiagnosed as medically unexplained dyspnoea: A case report. Issue 48 (December 2017) - Liao, Hao; Pei, Wendi; Liu, Junfang; Wang, Kai; Xu, Tingting; Chen, Xin
Abstract: Rationale: Secondary systemic lupus erythematosus (SLE) is an exceedingly rare complication of thymoma resection and is difficult to diagnose because of the insidious and nonspecific clinical manifestations. A case of SLE that occurs secondary to thymoma resection is described in this report. Patient concerns: A 43-year-old male came to our hospital with the sole symptom of dyspnea after thymoma resection initially. However, other atypical lesions of SLE occurred over time. Diagnoses: Antinuclear antibody spectrum test showed positive results and the diagnosis of SLE was obtained. Interventions: Initially the patient was treated for medically unexplained dyspnea (MUD) without much improvement. Following the diagnosis, the methylprednisolone pulse therapy and therapies of immunoglobulin and cyclophosphamide were adopted for the treatment. Outcomes: Finally, the patient's symptoms faded rapidly and favorable prognosis has been maintained till now. Lessons: This case highlights the importance of a serious and comprehensive analysis before we give the diagnosis of MUD. Additionally, ignorance of secondary SLE after thymoma resection should be prevented to avoid a delayed diagnosis and treatment.